Martha Stewart Living Omnimedia, Inc. : an accusation of insider trading (B) - Westby, Arianne R.; Moulton, Mary P.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Domestic advice and home products maven Martha Stewart is accused of selling nearly 4,000 shares of ImClone Systems, Inc. stock shares, just ahead of a public announcement that the companys promising new drug, Erbitux, has failed FDA clinical testing. Accusations of insider trading, based on her special relationships with ImClone CEO Samuel Waksal and Merrill Lynch broker Peter Bacanovic, threaten her own companys reputation, share price, and market position. Can Martha Stewart Living Omnimedia survive accusations of misconduct or the downfall of its namesake?
Originally published: Westby, A. R., Moulton, M. P., & ORourke, J. S. (2002). Martha Stewart Living Omnimedia, Inc.: An accusation of insider trading (B). 02-15 (B). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Stewart, Martha; Martha Stewart Living Omnimedia; Businesswomen -- United States; Corporations -- Corrupt practices -- United States